The impact of intrinsic foot muscle strengthening exercises in asymptomatic athletes with normal foot structure: A systematic review - Maha Ahmed; Saima Zaki; Md Farhan Alam; Saurabh Sharma; Abdulaziz Ali Al Salman; Ali Altaweel; Nazar Alkhadrawi; Shibili Nuhmani; Humaira Khan (Elsevier, 2024)
Purpose: The intrinsic foot muscles (IFM) are crucial to the passive, active, and neurological subsystems that compose the foot core, and their weakness may predispose to various foot pathologies, systemic diseases and musculoskeletal conditions. Strengthening of IFM is an effective intervention in clinical conditions, but its role in sports and clinical rehabilitation is still inconclusive. Thus, this review aims to evaluate the effects of IFM strengthening exercises in athletes with normal feet. Methods: An electronic database search was conducted using Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science (WoS), Scopus, MEDLINE, PubMed, and the Physiotherapy Evidence Database (PEDro). The Cochrane risk of bias tool was used for assessing bias in the included studies. Results: Four studies were included for qualitative review. The meta-analysis was not possible due to the heterogeneity of measuring units of outcome measures in the included studies. All the studies showed an improvement in intrinsic foot muscle strength, though the training protocols used by them were only roughly equivalent. One study reported no significant differences in MLA stiffness after 8 weeks of intervention. The clinician assessed motor performance and morphological assessments showed considerable improvements. Improved vertical running propulsive forces were reported, though the running economy showed no changes. Conclusion: Findings suggest that IFM exercises effectively improve outcomes such as foot morphology and function, strength, running mechanics and subjective function in athletes and may be incorporated in sports rehabilitation. These conclusions should be considered with caution due to bias in included studies.